Designing multilingual experiences in technical communication - Gonzales, Laura, author; Utah State University Press, publisher (Colorado State University. Libraries, 2022)
As technical communicators continue advocating for justice, the field should play closer attention to how language diversity shapes all research and praxis in contemporary, global contexts. Designing Multilingual Experiences in Technical Communication rovides frameworks, strategies, and best practices for researchers engaging in projects with multilingual communities.--Provided by publisher.
A "Theory of Change" for global technical communication -- An intersectional, interdependent approach to language accessibility in technical communication -- Research design -- Language fluidity in health contexts on the Mexico/US borderland -- User experience and participatory design in Kathmandu -- Linguistic and legal advocacy with and for indigenous language interpreters in Oaxaca -- Implications for designing multilingual experiences in technical communication.
Keywords: Communication of technical information -- Case studies; Multilingual communication -- Case studies; Technology -- Translating; Technical writing; Intercultural communication